Mr. Ganjar Roso's Traditional Therapy Based on Cultural and Religious Values from a Cross-Cultural Counseling Perspective - Talitha Laksmi Adibah (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: In a multicultural society like Indonesia, traditional medicine based on cultural and religious values plays a significant role as an alternative and complement to modern medical treatment. Objective: This study aims to describe the traditional therapy by Mr. Ganjar Roso in Banyumas, Central Java, from the perspective of cross-cultural counseling. Method: The research employs a qualitative descriptive approach, using data collection techniques such as direct interviews and documentation from the YouTube channel